1980
DOI: 10.1002/j.1537-2197.1980.tb07619.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Cephaleuros Virescens (Chroolepidaceae; Chlorophyta). Ii. Gametes

Abstract: Transmission electron microscopic examination of Cephaleuros virescens Kunze growing on leaves of Camellia sp. indicates that gametes are similar to those of Trentepohlia aurea. The gametes bear two, smooth isokont “keeled” flagella containing typical “9 + 2” axonemes and lacking scales. Flagellar insertion is apical and the parallel basal bodies overlap laterally. Each basal body is associated with a separate multilayered structure and component microtubular spline. The latter extends posteriorly beneath the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Structures observed paralleled those detailed in studies of Trentepohliales and Cephaleuros spp. [12,13,18,19]; however, in those studies, individual zoospores, isogametes, and/or meiozoospores were observed.…”
Section: Discussionmentioning
confidence: 79%
“…Structures observed paralleled those detailed in studies of Trentepohliales and Cephaleuros spp. [12,13,18,19]; however, in those studies, individual zoospores, isogametes, and/or meiozoospores were observed.…”
Section: Discussionmentioning
confidence: 79%